Reviews of recent publications (Studies in 20th & 21st Century Literature, 2013)
Kathyrn Everly. History, Violence, and the Hyperreal: Representing Culture in the Contemporary Spanish Novel by Nina L. Molinaro Jill Robbins. Crossing Through the Chueca: Lesbian Literary Culture in Queer Madrid by Salvador A. Oropesa Juan Pablo Dabove. Nightmares of the Lettered City: Banditry and Literature in Latin America 1816-1929 by María Zalduondo Federico Bonaddio. Federico García Lorca. The Poetics of Self-Consciousness by Carlos Jerez-Farrán Aníbal González. Love and Politics in the Contemporary Spanish American Novel by Mónica Adriana Agrest
Keywords: Contemporary Spanish novel; History; Violence; Hyperreal; culture; representation of culture; Lesbian Literary Culture; queer; Salvador A. Oropesa; Nina L. Molinaro; Banditry; Literature in Latin America 1816-1929; María Zalduondo; Poetics of Self-Consciousness; Poetics; Self-Consciousness; Carlos Jerez-Farrán; Love; Politics; Contemporary Spanish American Novel; Mónica Adriana Agrest